2004
DOI: 10.1590/s1677-55382004000300002
|View full text |Cite
|
Sign up to set email alerts
|

Role of intravenous urography and transabdominal ultrasonography in the diagnosis of bladder carcinoma

Abstract: Introduction: The present study was carried out to compare the efficacy of transabdominal ultrasonography and intravenous urography in the diagnosis of bladder carcinoma in those patients presenting painless hematuria.Materials and Methods: Medical records of 100 patients who had both ultrasonography and intravenous urography were studied. The reported findings of these investigations were correlated with those of cystoscopy.Results: Ultrasonography was significantly more sensitive (96%) in the detection of bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
10
0
4
Order By: Relevance
“…Age, gender and racial factors all affect the survival and prognosis of patients with bladder carcinoma [6]. In Pakistan, bladder carcinoma is one of the top 10 malignancies in men and most common urological malignancy in both sexes [7]. However, its clinicopathological features are not well described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Age, gender and racial factors all affect the survival and prognosis of patients with bladder carcinoma [6]. In Pakistan, bladder carcinoma is one of the top 10 malignancies in men and most common urological malignancy in both sexes [7]. However, its clinicopathological features are not well described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that ultrasound be used as a cost-effective method in cases of suspected bladder tumor. 17 Moreover, Hoenig and coworkers have shown the value of ultrasound in 5 boys aged 11 to 18 years with transitional cell carcinoma. 18 Ultrasound in the diagnosis of hematuria causes is able to show mucosal lesions greater than 4 mm to 5 mm when the bladder is full, while IVU could not show tumors smaller than 1.5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…(15,16,17,18) A small proportion of genes is extranuclear, as present in the mitochondria (cellular organelles that are inherited from the mother). (19,20,21,22) The alterations of mitochondrial and nuclear genes and, often, the interaction with environmental factors, contribute to identify five main groups of hereditary diseases. a) Chromosomal.…”
Section: Discussion:-mentioning
confidence: 99%